OP10 Comparing UK policies to reduce the consumption of ultra-processed foods: cardiovascular modelling study. (2nd September 2014) - Moreira, PVL; Baraldi, LG; Moubarac, JC; Monteiro, CA; O'Flaherty, M; Capewell, S
Abstract : Background: The world faces a growing burden of non-communicable diseases (NCDs). This partly reflects the global exposure to Ultra-Processed food Products (UPPs). UPPs are cheap, abundant, heavily marketed and convenient for consumers and highly profitable for manufacturers. However, the increasing production and consumption of UPPs is highly damaging to health due to their negative effects on the quality of the overall diet, including high levels of sodium, refined sugars, saturated fats and trans fats, high energy density, and low fibre content. This study therefore aimed to explore the potential mortality reduction associated with policies for substantially reducing future UPP intake in the UK. Methods: We obtained data from the UK Living Cost and Food Survey and from the National Diet and Nutrition. All food items were categorised into three groups, according to the nature, extent and purpose of food processing, following the validated NOVA food typology. [Group 1 ("Healthy") was unprocessed or minimally processed foods, Group 2 ("Ingredients") was processed culinary ingredients and Group 3 ("UPPs") was ready-to-consume processed or ultra-processed products]. Using UK nutrients conversion tables, we estimated the energy and nutrient profile of each group. The change in nutrient profile resulting from a partial or complete shift from Group 3 to Group 1 was then translated into reductions in cardiovascular mortality using the IMPACT Food Policy model. We then conducted a probabilistic sensitivity analysis using Monte Carlo simulation. Results: In 2030, approximately 175, 000 cardiovascular disease (CVD) deaths will occur if 2010 age-specific rates persist. However, if the intake of sodium, saturated fat and trans-fat in Group 3 was reduced to the levels observed in Group 1, it would lead to approximately 30, 000 fewer CVD deaths (minimum estimate 16, 400, maximum estimate 45, 600) in 2030, a 17% mortality reduction. This would comprise approximately 13, 100 fewer coronary heart disease (CHD) deaths (min 7100, max 19, 900), and 5500 fewer stroke deaths in men (min 3006, max 8510); and approximately 6700 fewer CHD deaths (min 3600, max 9900), and 4800 fewer stroke deaths in women (min 2600, max 7100). Conclusion: The potential reduction in CVD burden attainable with a healthier food system and dietary pattern is impressive. Although the complete elimination of UPPs is unlikely, even halving UPP consumption could still generate massive public health benefits. Comparable analyses might now be useful in low and middle-income countries which are currently experiencing aggressive UPP marketing and rapid nutritional transitions.